Terrorism: An Impediment To Socio-Economic Integration In Economic Community Of West African States (ECOWAS) - Dele, Ewemie Benedict; M.E., Emeto; Aminu, Abu (Archives of Business Research, 2018)
Nations are seeking avenues to play bigger role in the global economy and the world at large. One of such quests led to the formation of the Economic Community of West African States (ECOWAS) in 1975 by a – 15 – member nation to promote socio-economic integration among member countries. As a result, this body has encountered numerous challenges in its quest to move West African countries to the desired direction. One of such challenges which reared its ugly head not too long ago is terrorism. The emergence of terrorist groups such as Al-Qaeda in the Islamic Maghreb, the Movement for Unity and Jihad in West Africa (Mujoo), the Niger Delta Avengers, Ansar – Dine, Boko Haram and Juma’ata Ansarul Muslimina (Ansaru) and their activities within and around West Africa have become a matter of serious concern to governments and citizens of the region as their activities, being violent in nature, had negatively affected the flow of commerce and socio-economic interaction among Member States. This, of course has been identified by ECOWAS leaders as a major threat to the integration effort of the body. To this end, several regional mechanisms and instruments for enhancing security, development, good governance and counter terrorism activities were adopted by the body to stem the tide of crime and terrorism in the region. Among the security tightening measures to forestall terrorism and other forms of insecurity within the region include effective police to police co-operation in borderless communities, enhancement of police co-operation with the international police organization (INTERPOL), soliciting some intelligence agencies of the western world, as well as regional cooperation among security and intelligence agencies against terrorism. These measures, it is believed, would go a long way to check-mating the activities of terrorist groups and criminal gangs in the region, thereby enhancing and promoting the socio-economic interaction among member states. This paper work concludes that regional integration in ECOWAS is necessary if West African countries must play crucial role in the global economy and occupy a crucial position among the committee of nations. The paper recommends among others that ECOWAS as a body must re-strategize and enhance its security and intelligence apparatus for more proactive response to all forms of security threats and terrorism.